Warren Fahey folklore collection - Fahey, Warren (1969)
Folkloric recording
Recorded between 1969 and 2000.
Digital master available
Summary not yet available.
Keywords: Folk poetry, Australian; Folk songs, English -- Australia; Folklore -- Australia; Folk music -- Australia